The Complete Works of Artemus Ward $1 (BPart 7: Miscellaneouss - Ward, Artemus, 1834-1867 (Salt Lake City, UT : Project Gutenberg, 2002)
"The Complete Works of Artemus Ward $1 (BPart 7: Miscellaneous" by Artemus Ward is a humorous collection of essays and anecdotes written in the mid-19th century. Artemus Ward, the pen name of the American humorist Charles Farrar Browne, showcases his distinctive brand of satirical humor and social commentary through various short pieces, including travel logs, autobiographical sketches, and theatrical critiques. The book captures a whimsical portrayal of Ward's experiences, notably during his travels and his observations on society and culture. The opening of this collection introduces a series of amusing writings, starting with "The Cruise of the Polly Ann," where Ward recounts humorous anecdotes from a canal boat journey, including his interactions with eccentric passengers and the peculiar behavior of the boat's captain. The narrative is delivered in a playful, mock-phonetic style that enhances its comedic effect. Following this, subsequent sections present Ward's autobiographical reflections, skits centered around his theatrical life, and amusing commentaries on topics ranging from personal experiences to contemporary events, all rendered in his signature blend of wit and absurdity. The beginning sets the stage for the light-hearted and satirical tone that characterizes the entirety of the work, inviting readers into the entertaining world of Artemus Ward. (This is an automatically generated summary.)s
Release date is 2002-06-01
This etext was produced by anonymous Project Gutenberg Volunteers
Keywords: American wit and humor